Association between Antihypertensive Drug Use and the Incidence of Cognitive Decline and Dementia: A Meta-Analysis of Prospective Cohort Studies. (28th September 2017) - Xu, Guangli; Bai, Feng; Lin, Xin; Wang, Qiongying; Wu, Qiang; Sun, Shougang; Jiang, Cheng; Liang, Qiang; Gao, Bingren
Abstract : Background. Antihypertensive drug use is inconsistently associated with the risk of dementia, Alzheimer's disease, cognitive impairment, and cognitive decline. Therefore, we conducted a meta-analysis of available prospective cohort studies to summarize the evidence on the strength of these relationships. Methods. Three electronic databases including MedLine, Embase, and the Cochrane Library were searched to identify studies from inception to April 2017. Only prospective cohort studies that reported effect estimates with corresponding 95% confidence intervals (CIs) of dementia, Alzheimer's disease, cognitive impairment, and cognitive decline for antihypertensive drug use versus not using antihypertensive drugs were included. Results. We included 10 prospective cohort studies reporting data on 30, 895 individuals. Overall, participants who received antihypertensive drugs had lower incidence of dementia (relative risk [RR]: 0.86; 95% CI: 0.75–0.99; p = 0.033 ), while there was no significant effect on the incidence of Alzheimer's disease (RR: 0.83; 95% CI: 0.64–1.09; p = 0.154 ), cognitive impairment (RR: 0.89; 95% CI: 0.57–1.38; p = 0.596 ), and cognitive decline (RR: 1.11; 95% CI: 0.86–1.43; p = 0.415 ). Further, the incidence of Alzheimer's disease might be affected by antihypertensive drug use in participants with specific characteristics. Conclusions. Antihypertensive drug use was associated with a significantly reduced risk of dementia, but not with the risk of Alzheimer's disease, cognitive impairment, and cognitive decline.